Evaluating green Logistics through paradox - Tran, Mai Hương; Doan , Thị Vân; Pham , Trịnh Hồng Phi (Tạp Chí Khoa Học Và Công Nghệ Trường Đại Học Bình Dương, 2024)
In the modern transportation system, the important function is Logistics. Today's passenger and freight transport systems, thanks to developments in space and technology, have greatly improved in reliability, performance and cost. At the same time, the negative environmental effects of transportation are widely recognized and are central to sustainability issues, especially in urban areas. When today's logistics applications tend to be more positive and environmentally friendly, performance is also significantly improved in the system. This is what gave birth to the concept of "green logistics". It is said that although logistics may involve less environmentally harmful transport systems, they have created a series of paradoxes that may prove to be the opposite of what is believed. The article aims to review documents about "green logistics", thereby selecting information sources to further evaluate this concept through the paradoxes that the concept presents during its operation.